Multimedialny słownik lingworealioznawczy – nowe narzędzie w lingwokulturologii stosowanej - Olechno-Wasiluk, Joanna (Acta Polono-Ruthenica, 2018)
The paper constitutes an attempt to delineate the main assumptions, aims and research subject of applied linguo-cultural studies. This discipline works on the border of theoretical linguocultural studies and methodology of teaching a foreign language. The paper presents Multimedia Linguo-cultural Dictionary available on the webpage of Pushkin State Russian Language Institute. The author analyses the macro- and microstructure of the dictionary, focusing on its innovativeness. Entries in the dictionary are described in their entirety, considering references to the real world, which are essential in the socio-cultural functioning of every language, its description and teaching. This helps realise the main assumptions and aims of applied linguo-cultural studies.